1993
DOI: 10.1093/jnci/85.6.465
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Risk of Oral and Pharyngeal Cancer: Alcohol, Tobacco, and Other Determinants

Abstract: These findings suggest that the key to prevention of oral and pharyngeal cancers among both Blacks and Whites is reduced intake of alcoholic beverages and, because of strong interactive effects, the cessation of smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
146
1
5

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(161 citation statements)
references
References 19 publications
9
146
1
5
Order By: Relevance
“…Our AA patients were more likely to be smokers and heavy drinkers as compared with our CA cohort. This has been substantiated in previous studies, including that of Day et al, 13 who evaluated data from a large, population-based case-control study of oral cancer risk factors conducted in 4 areas of the United States. They found that AA patients were more likely to smoke and abuse alcohol compared with the CA patients in their population of SCCHN.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our AA patients were more likely to be smokers and heavy drinkers as compared with our CA cohort. This has been substantiated in previous studies, including that of Day et al, 13 who evaluated data from a large, population-based case-control study of oral cancer risk factors conducted in 4 areas of the United States. They found that AA patients were more likely to smoke and abuse alcohol compared with the CA patients in their population of SCCHN.…”
Section: Discussionsupporting
confidence: 52%
“…There have been numerous hypotheses published as to the etiology of this racial disparity. [10][11][12][13][14][15] Specifically, factors such as socioeconomic status, unequal cancer directed therapy, and advanced stage of presentation have been sited as an explanation for the poor outcomes in AA patients. [14][15] In 2006, Gourin and Podolsky published data from a nonrandomized retrospective cohort analysis to determine whether racial disparities exist between black and white patients with SCCHN treated at a single large institution in the South.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that genetic factors play a significant role in determining risk for both cancer and coronary heart disease (198,199) and behavioral factors such as cigarette smoking and heavy consumption of alcohol also influence susceptibility to these diseases (199)(200)(201). Nevertheless, when these factors are taken into consideration, dietary caloric consumption may be one of the most important risk factors for a spectrum of human degenerative diseases (4,202), and human epidemiology studies have established that increased body weight-or body mass index (BMI)-is positively correlated to a number of morbidity/mortality indices.…”
Section: Influence Of Caloric Intake On Human Morbidity and Mortalitymentioning
confidence: 99%
“…Estes tumores são representados em 90 a 95% dos casos pelo carcinoma epidermóide [1][2][3][4][5][6][7] . Acometem com mais freqüência o sexo masculino na 5ª e 6ª décadas de vida 8 , sendo em 80% atribuído a fatores ambientais, dietéticos, ocupacionais, infecção viral, fator imunológico e alterações genéticas 9,10 . Porém, o fator de risco dominante e comum a quase todos os portadores de câncer de orofaringe continua sendo o consumo de bebida alcoólica em associação ao tabaco 1,7,[11][12][13][14][15][16][17] .…”
Section: Introductionunclassified